Assessing and measuring statistics cognition in higher education online environments emerging research and opportunities - Chase, Justin P. 1987-; Zheng, Yan 1972- (Advances in higher education and professional development (AHEPD) book series, 2017)
"This book explores the fundamental understanding of learning statistics efficiently and effectively has a lot to do with how students think about statistics, how statistical cognitive processes influence student learning, what type of environments are conducive to developing statistics cognition, when emotions, moods, and attitudes can enhance or harm statistics cognition, and other topics"...